Business Vitality Initiative : Community Handbook - Community Economic Development and Employability Corporation (CEDEC) (2010)
If you’re not asking these questions, it’s unlikely you’re maximizing the potential of your community. Communities identifying their strengths, their gaps and their unexplored opportunities— that is what’s behind the BVI, a measurement and action process that helps communities harness their business potential. It has been designed to help communities assess their capacity to work with and support entrepreneurs, and to foster business growth. The BVI has been employed in communities across Canada (and recently in Australia) by a team based in Nelson, BC. The CIEL/BVI Team has been nominated for BC’s top award in community economic development and most recently won an award as the region’s most innovative organization. The BVI measures the perceptions of community leaders, business people and citizens about the current business environment in the community and compares the scores to those from other communities using a unique graphical index (the Business Vitality Index).

Business Vitality Initiative : Facilitator Handbook - Community Economic Development and Employability Corporation (CEDEC) (2010)
The Purpose of this Manual: The BVI includes two highly structured public meetings which require expert facilitation. This manual is a basic resource for facilitators. Other necessary resources include: • The BVI PowerPoint presentation • The BVI Community Handbook • Discussions with CIEL management • Discussions with the Community Sponsor • A BVI Assessment Report and Final Report from another community

Tourism 2025 : CEDEC's Plan for Creating 46,900 Jobs and Adding $5.2 Billion to the Economy - Community Economic Development and Employability Corporation (CEDEC) (2017)

Tourisme 2025 : Le plan de la CEDEC pour cré2r 46 9000 emplois et ajouter 5.2 milliards de dollar à l'économie - Community Economic Development and Employability Corporation (CEDEC) (2017)

Business vitality initiative : Manuel de l'animateur - Community Economic Development and Employability Corporation (CEDEC) (2010)
Le Business Vitality Initiative (BVI) comprend deux assemblées publiques très structurées qui doivent être animées par un expert. Le Manuel est la ressource principale des animateurs de ces assemblées, mais d’autres ressources sont aussi mises à leur disposition, notamment : • le diaporama sur le BVI; • le Manuel de la communauté – BVI; • le compte rendu des discussions avec la direction du CIEL; • le compte rendu des discussions avec l’organisme de parrainage communautaire; • un rapport d’évaluation dans le cadre du BVI et le rapport définitif d’une autre communauté.

English-Speaking Quebecers : Views on Governance - Quebec Community Groups Network (QCGN); Community Economic Development and Employability Corporation (CEDEC); Quebec English School Boards Association (QESBA); Association for Canadian Studies (ACS) (2019)
Keywords: Official Language Minority Community (OLMC)

English-Speaking Quebecers: Views on School Boards - Quebec Community Groups Network (QCGN); Community Economic Development and Employability Corporation (CEDEC); Quebec English School Boards Association (QESBA); Association for Canadian Studies (ACS) (2019)
Keywords: Official Language Minority Community (OLMC)